The Effect of High Population Growth on Physical Environment in Bufundi Sub-County Rubanda District. - Tumuheki, Alexander (Kabale University, 2024)
The study was about the effect of High population growth on the physical environment with specific reference to Bufundi Sub County. The study was based on the following research objectives; to find out the cause of population growth in Bufundi sub county, Rubanda District, to investigate the effects of high population on the physical environment in Bufundi Sub County, Rubanda District, and to suggest possible measures of controlling high population growth and improving the physical environment in Bufundi Sub County, Rubanda District. The study used a case study research design to collect and analyze data. The study used a sample size of two hundred and ten (210) respondents who included; political leaders, community members, and the sub-county chief. They used questionnaires and Interview guides as research instruments for data collection. Data was collected, analyzed, and presented using frequency distribution tables. From the findings a conclusion was drawn as follows; High population has a significant impact on the physical environment; as it leads to deforestation, soil degradation due to landfills, and depletion of natural resources. Finally, many recommendations were made as follows; Public community partnership, mitigating environmental degradation, and Public-private Voluntary Organisation Partnerships to curb the ever-increasing population.